Modern principles of organisation of university museums and exhibition spaces - Anna V. Vasileva (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. Today, many university museums around the world are facing the need to revise the principles of their activities in order to fully integrate into the daily life of their educational institutions. The main functions for such museums are patriotic, image-building, educational, educational and career guidance. Modern challenges include attracting not only students and applicants, but also a wider audience. Challenges of introducing new technologies will make them more relevant to younger generation. However, without defining the main purpose of the museum’s existence, it is impossible to build a coherent path for its development.Purpose. To determine the basic principles of exhibition organisation and its placement in the structure of a university campus, depending on the nature of the museum and the image of the educational institution.Results. Using the example of museums of the world’s largest universities, the specifics of their location depending on specialisation, the correlation between the organization of space and the theme of the exhibition, the characteristics of exhibition equipment, the principles of placement of different types of expositions in the structure of campuses are determined.Conclusions. It has been found that when the university is image oriented towards history and traditions, the museums are located in historical buildings and have a more familiar spatial structure and principles exhibition organization. In the case of striving to demonstrate the innovative nature of the university, the priority is given to the placement in the most accessible and technologically advanced modern buildings. Exhibitions related to the current life of the university are housed in more light, versatile and democratic spaces. The latest trend is the active use of multimedia and interactivity.